ANALISIS PENERAPAN ELECTRONIC MEDICAL RECORD (EMR) DI POLIKLINIK GIGI DAN MULUT RUMAH SAKIT UMUM DAERAH WANGAYA KOTA DENPASAR - Vrinda Rani Rani Vrinda Rani (Health Care Media, 2024)
Minister of Health Regulation No. 24 of 2022 requires all health facilities to use electronic medical records. Based on initial observation results, the implementation of services in dental and oral clinics still uses paper medical records, and the EMR cannot be used optimally. To be able to maintain the quality of information and user comfort regarding EMR, an assessment or analysis of the implementation of Electronic Medical Records is needed using the Technology Acceptance Model (TAM) method which aims to see the acceptance of EMR users at the Dental and Oral Polyclinic at Wangaya Hospital, Denpasa City. is Spearman's Rank Correlation analysis. The results show that based on perceived ease of use (PEOU) and perceived usefulness (PU), 16 respondents (47.1%) felt that using EMR provides convenience and is useful in various operational and operational aspects. patient related information. Based on perceptions of attitude towards use (ATU) and actual conditions of system use (Actual System Usage (ASU)), 21 respondents (61.8%) felt that EMR could help manage patient data and access medical information more quickly and effective. Hypothesis testing shows that there is a relationship between the implementation of EMR and the level of user acceptance. The suggestion is to continue to improve monitoring and evaluation of EMR. For future researchers